Public policy towards the sale of state assets in troubled times: Lessons from the Irish experience - Paul K. Gorecki; Sean Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
Governments throughout the western world and beyond are in the midst of a severe financial crisis and emerging from a sharp recession. Ireland is no exception. One of the options for strengthening public finances is the sale of state assets. In this paper we draw on the Irish experience to inform the wider debate on this important issue. Debate over the potential saleability of certain tangible and intangible assets owned by the state turns into much more than an exercise in ranking these assets by commercial viability and value. Careful attention needs to be devoted to ensuring that wider public policy considerations are taken into account, such competition, regulation and economic development. Hence it is important to formulate terms of reference for any consideration of the sale of state assets that reflect these wider concerns. In the case of tangible assets - commercial state firms - the debate is around whether these firms should be the public sector and whether the objectives can be better met by alternative arrangements. In privatising these state-owned firms careful attention needs to be paid to ensure that markets are well organised and competitive. This may necessitate for example breaking up a vertically integrated firm into its competitive and monopoly parts. To a considerable degree the debate over privatisation reflects issues related to the regulatory reform agenda. But in both cases what is on offer is a more efficient and competitive economy if reform is conducted sensibly and is not derailed by vested interests as has been the case, on occasion, in the past. In terms of intangible assets such as permits of various kinds such a those relating to carbon, wind turbine and oil exploration as well as radio spectrum licences, the conclusion is much more straightforward: these assets should be auctioned off to the highest bidder, but using a carefully designed auction which needs to take into account the competitive situation amongst the bidders not only to prevent collusion and gaming, but also to encourage entry and competition. Another important reason to auction these assets is that there is a danger, absent auctioning, that government will be unaware that these are valuable assets and hence not properly price them when making public policy decisions.
Keywords: 330; privatisation; regulation; competition; tangible assets; intangible assets; Ireland; intangible state assets; tangible state assets; Wirtschaftskrise; Öffentliche Schulden; Öffentliche Einnahmen; Öffentliches Vermögen; Verkauf; Irland